Gangguan Keterlambatan Berbicara (Speech Delay) pada Anak Usia Dini - Sicilia Desiarna; Ulfa Nafila; Restiani Restiani; Fatmawati Fatmawati (UIR Press, 2023)
Discourse defer in youth is a condition where the quality the kid's discourse improvement is unseemly or under his age, where is the kid experiences issues communicating his sentiments and needs dominance jargon for kids. The motivation behind this exploration is to comprehend too depict discourse postpones experienced by youth. Subject in this study added up to 1 kid, who experienced discourse delays. The sources of this study were chosen involving a purposive strategy with measures for youth matured 3-6 years, experienced discourse delays, and in view of the proposal of the class educator. Information assortment was acquired from essential witnesses to be specific kids who experience discourse delays. Information examination strategies utilized utilizing graphic account methods to make sense of the outcomes study. In light of the consequences of the examination it tends to be reasoned that the postponement discourse experienced by youth causes a few impediments including the youngster is less ready to express out loud whatever he feels or what is he needs, the kid feels abnormal to get the discussion together with his companions, and furthermore the youngster will in general be quiet. Imperatives are likewise felt by the kid's conversationalist like guardians, educators, or companions when need to converse with kids.